Microsoft Power BI untuk Analisis Data Pembelajaran Siswa di SMK Reformasi Kota Jakarta Barat - Wardhana, Ariyani; Hindardjo, Anton; Irvan, Muhammad (LPPM Universitas Bung Karno, 2024)
Data analysis is very crucial nowadays. Educational Institutions in order to improve services and better understand the conditions of the learning process of their students need more in-depth data analysis in order to get an overview of the condition of student learning outcomes, obstacles experienced, and opportunities to improve the quality and service of Education for their students. Data analysis can be done quite easily using power BI, where the raw data to be used can be in the form of excel that has been used by SMK Reformasi before. This will make it easier for partners to improve condition assessments with minimal changes to existing systems and more optimal efforts. On the occasion of this community service activity, we will explain and guide the teachers of SMK Reformasi so that they can use power BI to make reports and analyze data on their students. With increased understanding and application of deeper data analysis, it is expected to be able to apply the most appropriate teaching method for each subject taught. This will certainly have an impact on student learning outcomes and student satisfaction and parents as well as increased competition and reputation of SMK Reformasi.